Spontaneous Regression of Metastatic Papillary Thyroid Cancer in a Lymph Node. (20th March 2018) - Shim, Jien; Rao, Jianyu; Yu, Run
Abstract : Spontaneous regression of cancer is defined as disappearance of cancer in the absence of specific therapy. In thyroid cancer patients with biochemically incomplete response to initial treatments, spontaneous decline in thyroglobulin levels without any cancer treatment is a well-known phenomenon; however, spontaneous regression of persistent or recurrent structural disease has not been reported. We here present a case of papillary thyroid cancer in a 58-year-old female who underwent total thyroidectomy and two radioiodine ablations. She had persistently elevated thyroglobulin levels. Six years after her initial treatments, she had biopsy-proven cervical lymph node metastasis. The patient opted not to undergo any further treatment. Over the course of the next 10 years, without any additional treatment, the lymph node disappeared and her thyroglobulin levels decreased to almost undetectable ranges, implying near-complete regression. Our case illustrates that metastatic papillary thyroid cancer in lymph nodes can regress spontaneously.